The Contribution of Digital Entrepreneurial Competence to the Business Growth of Women-Owned SMEs in the Fashion Industry : JEL Classification: J16; L25; L26; M13; O33 - Krisdayanti Krisdayanti; Susilawati Susilawati; Irwandi Saputra (Maroon Journal De Management, 2026)
Digital competence and entrepreneurial ecosystems are constantly changing as a result of digital technology's continued rapid growth. The purpose of this study is to analyze the contribution of digital entrepreneurial competence in the growth of women owned small and medium enterprises (SMEs) in the fashion industry in Yogyakarta, Indonesia. The research method implemented is quantitative with the data obtained in the study from 120 women entrepreneurs of fashion SMEs who are consumers of the study. Digital entrepreneurial competence is split into four areas: digital literacy, digital innovation, online networking and digital tools utilization, and business growth is evaluated by sales growth, customer growth and brand awareness. According to multiple regression analysis, all the dimensions of digital entrepreneurial competence are positively and significantly associated with the growth of a business. Digitization tools usage and digital literacy prove to be the best predictors for SME growth, signifying the strategic relevance of being capable to put instruments into digital use and understanding the digital world. This study is novel in its multidimensional investigation into the case of digital entrepreneurship in the context of female entrepreneurs' fashion SMEs in a developing economy. The results are valuable not only for digital entrepreneurship literature, but also for practice for policy makers and stakeholders (SME development institutions) to design digital capacity-building programs for women entrepreneurs.